Horse riding - Evans, Jeremy (London : Heinemann, 1992)
Discusses many aspects of horses and horsemanship, including points of a horse, popular breeds, riding techniques, safety tips, and competitive events.
Includes index.
Elementary School Library Collection (Bro-Dart).
Horn Book Magazine.
6.4
5-8.
Keywords: Horsemanship -- Juvenile literature; Horses -- Juvenile literature; Ponies -- Juvenile literature; Horsemanship; Horses; Ponies; Horsemanship; Horses; Ponies